PENGARUH TATO, PERTUMBUHAN LABA, NPM, DAN LEVERAGE TERHADAP ROE PERUSAHAAN MAKANAN DAN MINUMAN DI BEI PERIODE 2020-2023 - Rahmawati; Faisol; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This study aims to analyze the effect of asset turnover, profit growth, profit margin, and leverage on return onequity. The dependent variable in this study is return on equity, while the independent variables include assetturnover, profit growth, profit margin, and leverage. Data were collected from companies in the food and beveragesubsector listed on the Indonesia Stock Exchange from 2020 to 2023. The research sample consisted of 10organizations selected based on certain criteria. The quantitative research method used is multiple linearregression analysis, using a 5% confidence level to explain the relationship between variables. The results of thepartial test show that the variables of asset turnover, profit growth, profit margin, and leverage greatly affect returnon equity. The findings of the simultaneous test show that the variables of asset turnover, profit growth, profitmargin, and leverage together have a significant effect on return on equity. The results of this study are expectedto be a reference for other companies listed on the IDX to prioritize financial ratios to increase profitability.